2017
DOI: 10.1097/md.0000000000006744
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiling in the dentate gyrus in epileptic rats

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
(64 reference statements)
2
7
0
Order By: Relevance
“…There appears marked global disparity in the treatment for epilepsy between high-and low-income countries; and between rural and urban regions (Meyer, Dua, Ma, Saxena, & Birbeck, 2010). Recently, several studies have reported that microRNAs (miRNAs) are emerging as a critical new layer of gene expression control with implications for the cause and treatment of epilepsy, such as miR-146a, miR-187-3p, and miR-129-5p (Aronica et al, 2010;Jimenez-Mateos and Henshall, 2013;Liu, Wu, & Wang, 2017;Zhang, Kou, Hu, & Han, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There appears marked global disparity in the treatment for epilepsy between high-and low-income countries; and between rural and urban regions (Meyer, Dua, Ma, Saxena, & Birbeck, 2010). Recently, several studies have reported that microRNAs (miRNAs) are emerging as a critical new layer of gene expression control with implications for the cause and treatment of epilepsy, such as miR-146a, miR-187-3p, and miR-129-5p (Aronica et al, 2010;Jimenez-Mateos and Henshall, 2013;Liu, Wu, & Wang, 2017;Zhang, Kou, Hu, & Han, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Four of these genes were differentially methylated in the opposite direction: Babam1 has been linked to schizophrenia 65 , Cacnb1 to autism 66 and depression 67 , Coro2b , a candidate gene for ciliopathies to intellectual disability 68 and Gmppa to intellectual disability and autonomic dysfunction 69 . Two genes that are differentially methylated in the same direction in males and females are Rusc1 whose gene product serves as neuronal adaptor protein 70 and Paqr4 which was recently associated with the development of epilepsy 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Target genes of miR-187-3p were involved in the regulation of signaling pathways, including phosphatidylinositol 3-kinase-AKT and hypoxia-inducible factor 1 signaling pathways in epileptic rats ( 44 ). Hendrix et al ( 45 ) revealed that FGF9 was a downstream target of the Wnt signaling pathway, which may be an indirect transcription target of β-catenin in ovarian endometrioid adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%